Accelerating global left-ventricular function assessment in mice using reduced slice acquisition and three-dimensional guide-point modelling. - Young, A; Medway, D; Lygate, C; Neubauer, S; Schneider, J (2011)
BACKGROUND: To investigate the utility of three-dimensional guide-point modeling (GPM) to reduce the time required for CMR evaluation of global cardiac function in mice, by reducing the number of image slices required for accurate quantification of left-ventricular (LV) mass and volumes. METHODS: Five female C57Bl/6 mice 8 weeks post myocardial infarction induced by permanent occlusion of the left coronary artery, and six male control (un-operated) C57Bl/6 mice, were subject to CMR examination under isoflurane anaesthesia. Contiguous short axis (SAX) slices (1 mm thick 7-9 slices) were obtained together with two long axis (LAX) slices in two chamber and four chamber orientations. Using a mathematical model of the heart to interpolate information between the available slices, GPM LV mass and volumes were determined using full slice (all SAX and two LAX), six slice (four SAX and two LAX) and four slice (two SAX and two LAX) analysis protocols. All results were compared with standard manual volumetric analysis using all SAX slices. RESULTS: Infarct size was 39.1±5.1% of LV myocardium. No significant differences were found in left ventricular mass and volumes between the standard and GPM full and six slice protocols in infarcted mice (113±10, 116±11, and 117±11 mg respectively for mass), or between the standard and GPM full, six and four slice protocols in control mice, (105±14, 106±10, 104±12, and 105±7 mg respectively for mass). Significant differences were found in LV mass (135±18 mg) and EF using the GPM four slice protocol in infarcted mice (p<0.05). CONCLUSION: GPM enables accurate analysis of LV function in mice with relatively large infarcts using a reduced six slice acquisition protocol, and in mice with normal/symmetrical left-ventricular topology using a four slice protocol.